High Throughput Quantitative Bioanalytical LC/MS/MS Determination of Gemifloxacin in Human Urine. (27th November 2013) - Kadi, Adnan A.; Angawi, Rihab F.; Attwa, Mohamed W.; Darwish, Hany W.; Abdelhameed, Ali Saber
Abstract : A highly specific, sensitive, and rapid method, to quantify gemifloxacin in human urine using HPLC coupled to the triple quadrupole mass spectrometer system, was developed and validated. Gemifloxacin and ofloxacin (internal standard) were rapidly extracted from urine samples without any tedious pretreatment procedure. Urine samples were filtered through a Millex-GP, 0.22  μ m syringe filter. Optimal chromatographic separation of the analytes was achieved on Zorbax SB-C18 (30 mm × 2 mm i.d., 3.5  μ m maintained at ambient temperature). The mobile phase consisted of 0.1% formic acid (pH 3.2) and acetonitrile (80 : 20) and a flow rate of 0.2 mL min −1 for 4 min. The analytes were monitored by electrospray ionization in positive ion multiple reaction monitoring mode. The method provided a linear response (r = 0.9998 ) from a quantitation range of 5 ng mL −1 to at least 500 ng mL −1 . The mean extraction recovery % of gemifloxacin from spiked human urine was 101.33 ± 2.58%. The reproducibility of the method was reliable with the intra- and inter-day precision of <2% and accuracy within 2%. The established method was reliably applied for the determination of gemifloxacin in volunteers' urine samples with the mean recoveries of gemifloxacin from Factive tablets 320 mg > 97.0%.